CONDITIONS, AIMS , CONTENT AND MEANS OF ELT AT HIGHER ADUCATION ESTABLISHMENTS , LYSEUM AND COLLAGES. - Moydinova Shohidaxon; Mirodiljonova Guliroza (TADQIQOTLAR, 2025)
This article explores the multifaceted dimensions of English Language Teaching (ELT) within higher education establishments, lyceums, and colleges. It examines the conditions required for effective ELT, the aims set forth by educational institutions, the content of ELT curricula, and the pedagogical means employed to achieve learning objectives. The discussion underscores the necessity of adapting ELT strategies to align with global standards, fostering communicative competence, and integrating modern technologies to enhance learning outcomes. Moreover, it provides an in-depth analysis of challenges faced in these contexts and offers practical solutions.